2020
DOI: 10.1002/cam4.2836
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and risk of subsequent breast events in breast‐conserving surgery patients with BRCA1 and BRCA2 mutation

Abstract: Purpose Previous studies provide inconsistent interpretations of the effect of inherited genetic factors on the survival and prognosis of patients with breast cancer. The aim of this study was to examine the effect of germline BRCA1 and BRCA2 mutation on survival and subsequent breast events in Chinese women who underwent breast‐conserving surgery. Methods A retrospective review of the clinical and pathological records was performed in patients diagnosed with primary invasive breast cancer between 2005 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It has been argued that most ipsilateral events are new primary cancers [ 125 ]. There is however an increased risk of contralateral breast cancer in women with BRCA mutation [ 33 , [115] , [116] , [117] , 126 , 127 ]. The risk is estimated to 25–30% over 10 years and more than 40% over 15 years ([ 33 , 126 ]).…”
Section: Surgical Procedures Associated With Female With Brca Mutationmentioning
confidence: 99%
“…It has been argued that most ipsilateral events are new primary cancers [ 125 ]. There is however an increased risk of contralateral breast cancer in women with BRCA mutation [ 33 , [115] , [116] , [117] , 126 , 127 ]. The risk is estimated to 25–30% over 10 years and more than 40% over 15 years ([ 33 , 126 ]).…”
Section: Surgical Procedures Associated With Female With Brca Mutationmentioning
confidence: 99%
“…Through prospective randomized trials, related studies have confirmed that BCS combined with SLNB in patients with lymph node-negative breast cancer has a better physical and psychological impact on patients than previous axillary lymph node dissection treatment, and lower occurrence rate of complications (17,18). In this study, the results showed that patients undergoing BCS combined with SLBN and axillary preservation treatment experienced significantly lower operation times, intraoperative blood loss, and extubation times than did the control group, with the quality of life after treatment being better than that of the control group; also, 93.42% of patients in the combined group gave a good or excellent rating for the postoperative cosmetic result, which as significantly higher than that given by the control group (P<0.05); no significant difference was found in the recurrence and metastasis rate compared with the control group, which was consistent with the results of previous studies (19).…”
Section: Discussionmentioning
confidence: 97%
“…By the age of 70 years, BRCA1 and BRCA2 carriers were previously found to have average cumulative risk of contralateral breast cancer of 83% and 62%, respectively [10]. Ye et al also showed higher risk of contralateral breast cancer in BRCA mutation carriers [39].…”
Section: Discussionmentioning
confidence: 98%